The Role Of Investment In Education In Enhancing Economic Welfare - Faris, Moh.; Nilasari, Aprillia (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to explore the role of education as an investment in enhancing economic welfare. The study investigates how education, as a crucial component of human capital, contributes to economic well-being by promoting economic growth, job creation, productivity improvement, and reducing income disparities. Utilizing qualitative methods with a literature review approach, this study evaluates empirical evidence supporting the positive relationship between investment in education and various economic benefits. The findings indicate that investment in education significantly impacts economic growth by increasing workforce productivity, stimulating innovation, and reinforcing economic infrastructure. Furthermore, education investment fosters job creation by enhancing workforce skills, supporting the education and training sector, and promoting innovation and entrepreneurship. Additionally, the study highlights that quality education enhances productivity by developing technical, analytical, and creative skills, improving resource utilization, and facilitating technological adoption. Lastly, the research underscores that investment in education reduces income disparities by ensuring equal access to education, increasing social mobility, and reducing skill gaps. The policy implications emphasize the need for sustainable education investments, strengthening skill training, and fostering an environment conducive to innovation and entrepreneurship. This study provides essential insights for policymakers to design inclusive and sustainable economic growth strategies, demonstrating that education is a pivotal investment for enhancing the economic well-being of communities.